KLF10 affects pancreatic function via the SEI-1/p21Cip1 pathway. (March 2015) - Wu, Min-Ju; Wu, Wen-Chi; Chang, Hsuen-Wen; Lai, Yong-Tzuo; Lin, Ching-Hui; Yu, Winston C.Y.; Chang, Vincent H.S.
Abstract: TGF-β plays a significant role in regulating pancreas islet function and maintaining their mass. KLF10, a TGF-β downstream gene, belongs to a group of Krüppel-like transcription factors that bind to the promoters of target genes and produce effects that mimic TGF-β as a tumor suppressor. Using ChIP-chip screening, SEI-1 was identified as a target gene that may be regulated by KLF10. We conducted a series of assays to verify the presence of unknown regulation events between SEI-1 and KLF10. These showed that KLF10 transcriptionally activates the SEI-1 promoter and, furthermore, induces SEI-1 protein expression in pancreatic carcinoma cells. SEI-1 is one of the key factors involved in cell cycle control through the regulation of other transcription factors such as the p21 Cip1 gene. Interestingly, it has been shown previously that p21 Cip1 is indirectly activated by KLF10. Our results first demonstrated that KLF10 acts as a transcriptional activator on SEI-1, which can then result in increased p21 Cip1 expression. Furthermore, KLF10-deficiency in mice is associated with a decrease in the pancreatic islet mass, which is similar to the effects found in SEI-1 deficient mice. The KLF10-defect was also associated with the nuclear accumulation of the p21 Cip1 in islet cells. Based on our molecular and histological findings, we conclude that KLF10 plays an important role in pancreatic β-cells and this supports a functional link between KLF10 and various cell cycle regulators, most notably in the context of the pancreas.